Evaluation of arthroscopic pull-through fixation in posterior cruciate ligament avulsion fractures: clinical and radiological results from a case series - Ritwika Nandi; Pinaki Das; Pravash Ranjan Parida; Durga Kanta Sahoo; Deepak Kumar Nayak (International Surgery Journal, 2026)
Posterior cruciate ligament (PCI) avulsion fracture is a rare type of ligamento osseous injury which is usually caused by high velocity injuries. The objective of this case series is to evaluate the improvement of knee function over time by measuring Lysholm knee score of patients treated by arthroscopic pull through fixation technique. This is a case series study of patients with PCI avulsion fractures from January 2024 to December 2025. All the patients were subjected to a single tibial tunnel pull through fiber tape fixation of the PCL over the anterior aspect of tibia. The results were analyzed by measuring knee ROM and Lysholm score over time and clinico-radiological confirmation of bony union. The patients which were included in the study consisted of 9 males and 1 female. Mean age of all the patients came around 37.6. The average knee flexion of all the patients at 6 weeks was 82 degrees, at 12 weeks was 124 degrees, at 6 months-128 degrees and at the end of 12 months was almost 130 degrees. None of the patients had any sort of extension lag. Radiological union was determined over serial X-rays and none of the study participants had non union. The mean Lysholm knee score at 6 weeks was 72.6, at 12 weeks was 80, at 6 months-88.2 and at end of 12 months it came around 95. Arthroscopic pull through fixation of PCI Avulsion fractures yielded good results with satisfactory knee function over time and faster rehabilitation.